Spatial Patterns of Food Security in Haryana: A District-level Analysis (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
In today's era the issue of food security is gaining much more attention as foodis one of the three basic requirements of man and is still a serious issue formany poor people. Ensuring food security is a big challenge due to increase inpopulation, climate change etc. especially in developing Asian countries likeIndia. The present study is significant in a way that it examines the variationsin spatial patterns of food security at district level in one of the food bowlstates of India namely Haryana. This study also tries to identify the factorsbehind the spatial variations in food security. Despite being self-sufficient infoodgrains production, the state has vast regional contrasts in terms of landproductivity, farm labour and standard of living. At present, food grainsproduction is almost stagnant in the state and natural resources are alsoexperiencing degradation due to their extensive use. For this study, secondarydata have been collected from various state government offices. Further foodavailability, food accessibility and food utilization indices have beencalculated by using different indicators. The results of the study reveal that thedistricts situated in central and north-west part of the state having betteragricultural infrastructure are more food secure than the districts situated insouthern and northern parts of the state which have the disadvantageous thestate which have sandy soil, poor irrigation facilities and undulatingtopography.
Keywords: Food accessibility; Food availability; Food security index; Topography; Food utilization